TANK-Binding Kinase 1-Dependent Responses in Health and Autoimmunity - Louis, Cynthia; Burns, Chris; Wicks, Ian (Frontiers in Immunology, 2018)
The pathogenesis of autoimmune diseases, such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) is driven by genetic predisposition and environmental triggers that lead to dysregulated immune responses. These include the generation of pathogenic autoantibodies and aberrant production of inflammatory cytokines. Current therapies for RA and other autoimmune diseases reduce inflammation by targeting inflammatory mediators, most of which are innate response cytokines, resulting in generalized immunosuppression. Overall, this strategy has been very successful, but not all patients respond, responses can diminish over time and numerous side effects can occur. Therapies that target the germinal center (GC) reaction and/or antibody-secreting plasma cells (PC) potentially provide a novel approach. TANK-binding kinase 1 (TBK1) is an IKK-related serine/threonine kinase best characterized for its involvement in innate antiviral responses through the induction of type I interferons. TBK1 is also gaining attention for its roles in humoral immune responses. In this review, we discuss the role of TBK1 in immunological pathways involved in the development and maintenance of antibody responses, with particular emphasis on its potential relevance in the pathogenesis of humoral autoimmunity. First, we review the role of TBK1 in the induction of type I IFNs. Second, we highlight how TBK1 mediates inducible T cell co-stimulator signaling to the GC T follicular B helper population. Third, we discuss emerging evidence on the contribution of TBK1 to autophagic pathways and the potential implications for immune cell function. Finally, we discuss the therapeutic potential of TBK1 inhibition in autoimmunity.